Activity of the Novel Extended-spectrum β-Lactamase Inhibitor AAI101 in Combination with Cefepime Towards a Challenge Panel of Acinetobacter baumannii. (4th October 2017) - Morrissey, Ian; Magnet, Sophie; Hawser, Stephen; Shapiro, Stuart; Seifert, Harald; Higgins, Paul
Abstract: Background: AAI101 is a novel extended-spectrum β-lactamase inhibitor (BLI), active against ESBLs and a broad array of other BLs. AAI101 in combination with cefepime (FEP) is in Phase 2 development. Infections caused by A. baumannii, a pathogen endemic to the southern US and other global regions, are very challenging to treat, and often require combination therapy. This study examined the activity of FEP/AAI101 against a challenge set of A. baumannii clinical isolates enriched with OXA carbapenemase producers. Methods: BLs in A. baumannii were identified by genotyping. Broth microdilution MICs and susceptibilities were obtained following CLSI methods and breakpoints (BPs), except for ceftazidime-avibactam (CAZ/AVI) where FDA P. aeruginosa BPs were used. CLSI FEP BPs were used for FEP/AAI101. Results: All OXA-51 producers had the ISAba1 promoter. MIC90 data and % susceptibilities (%S) for FEP/AAI101 and comparators are shown in the Table: FEP/AAI101 was highly active against meropenem-susceptible (MPM s ) isolates. FEP/AAI101 (AAI101 fixed at 8 µg/ml) covered 67% of OXA-51 and 53% of OXA-58 strains. Lower susceptibilities were obtained for OXA-23 and OXA-24/40 producers. FEP/AAI101 was the most active β-lactam product. Colistin (COL) was the only agent with consistently high activity against all A. baumannii isolates. Conclusion: FEP/AAI101 was the most potent β-lactam product tested against clinical isolates of A. baumannii producing OXA-51 and OXA-58 β-lactamases. Infections by this difficult pathogen often require combination therapy, of which FEP-AAI101 may be a component. Disclosures: S. Shapiro, Allecra: Employee, Salary